The Role of the Heritage of the Uzbek Folk Musical Culture in the Development of the Culture of the Peoples of the East - qizi, Rustamjonova Dilkhavas Ravshanbek (Research Parks Publishing LLC, 2023)
This article presents the role of the ancient musical heritage of the Uzbek people in the development of oriental musical culture, the history of the development of performing arts, the theory of musical science, the opinions and information of scientists.